The Contrastive Analysis on the Affixes of Betawi Dialect and Bahasa Indonesia - Indrie Harthaty (Budapest International Research and Critics University, 2022)
Language is a form of communication that everyone uses in their social environment. If we understand their language, we can easily respond to what others say. We have learned the language since we were children from our parents and it is our mother tongue. Language is also used for informal or formal communication in everyday life and in the office, be it formal or informal communication and so on. This thesis is aqualitative research that refers to the linbruistic analysis on the affixes of Betawi dialect (a case study on Selto Wargo, Lcnong Betawi). The writer uses Lenong Betawi as the subject of her thesis because Betawi dialect is still commonly used in their conversation. Morphological processes are divided into three groups, namely attachment, complication and compounding. In this chapter, the author describes the accessories for the bctawi ctialek. The calendar procedure consists of prefixes, suffixes, and merging. The conclusion of this study is that the morphophonmic process that occurs in the prefix he(r)- Betawi dialect is the process of eliminating the consonant /r/ into the affix be-. This happens when the root that follows it starts with all consonants except root which starts with /1/ and /r/.